Local knowledge matters : power, context and policymaking in Indonesia - Nugroho, Kharisma; Carden, F. (Fred); Antlöv, Hans (Policy Press shorts. Research., 2018)
"Available Open Access under CC-BY-NC licence. This book explores the critical role that local knowledge plays in public policy processes as well as its role in the co-production of policy relevant knowledge with the scientific and professional communities. The authors consider the mechanisms used by local organisations and the constraints and opportunities they face, exploring what the knowledge-to-policy process means, who is involved and how different communities can engage in the policy process. Ten diverse case studies are used from around Indonesia, addressing issues such as forest management, water resources, maritime resource management and financial services. By making extensive use of quotes from the field, the book allows the reader to 'hear' the perspectives and beliefs of community members around local knowledge and its effects on individual and community life."